Darurat Perlindungan Kaum Difabel Korban Kekerasan Seksual - Shafiyyah Tamala Yunfa; Dhea Amalia Khofivantunnisa (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This article discusses the issue of disabled people as victims of sexual violence and how the law in Indonesia protects disabled people. The number of disabled people in Indonesia has increased from year to year. This triggers the vulnerability of disabled people as victims of sexual violence because of the physical, mental and social barriers they have. Persons with disabilities are among the parties who have the right to obtain legal assistance under the law. Even though there are laws that regulate the protection of disabled people, in reality there are still victims of sexual violence against disabled people who are neglected. This proves that there are still many challenges in providing legal assistance to crime victims with disabilities. Normative juridical research method with a statutory approach. The importance of states in providing the necessary resources and training for legal aid agencies to support victims with disabilities, to ensure that victims with disabilities are aware of their legal rights, and to ensure that law enforcement officers are trained to handle cases involving victims with disabilities disability. So that people with disabilities can feel justice and security in living their lives in this legal country, Indonesia.